Monitoring the Influence of Sunlight on the Oxidative Stability, Color, and Fatty Acid Composition of Sunflower, Sesame, Groundnut, Mustard, and Rice Bran Oils - Fabrice Tonfack Djikeng; Veshe‐Teh Zemoh Sylvia Ninying; Mallampalli Sri Lakshmi Karuna; Leslie Asobo Forlemu; Hilaire Macaire Womeni (Future Postharvest and Food)
ABSTRACT The objective of this study was to assess the effect of sunlight on the oxidative stability, color, and fatty acid composition of sunflower, sesame, groundnut, mustard, and rice bran oils compared to ambient dark conditions. Oil samples were exposed to sunlight and ambient conditions for 90 days. The samples were collected after every 30 days for quality analysis [peroxide value (PV), p‐anisidine (p‐AnV), total oxidation (TOTOX), thiobarbituric acid (TBA), free fatty acid (FFA) values, induction period on Rancimat, color, and fatty acid composition]. Results showed that sunlight significantly increases the formation of primary and secondary oxidation products as well as the hydrolysis rate of sesame, mustard, sunflower, groundnut, and rice bran oils compared to ambient dark conditions. In the same line, it significantly reduces the color and oil resistance to oxidation (induction time) compared to ambient dark conditions. However, sunlight did not affect the fatty acid composition of these oils. Looking at the oils amongst themselves, rice bran oil was the most affected oil in terms of the TOTOX value. Oils should not be exposed to sunlight in order to preserve their quality.